Effects of hydrogen peroxide on growth, development and quality of fruits: A review - Nashriyah, Mat; Mohammad Moneruzzaman, Khandaker; Siti Zuriani, Ismail (Asian Network for Scientific Information, 2015)
There is increasing concern about the effects of hydrogen peroxide (H2O2) on plant growth and development as well as fruit quality, worldwide. Hydrogen peroxide is produced predominantly in plant cells during photosynthesis and photorespiration and also in respiration processes. It is most stable of so-called Reactive Oxygen Species (ROS) and therefore, plays crucial role as signaling molecule in various physiological process. Increment of intra- and intercellular levels of H2O2 give effect on growth, development and quality of fruits with the optimum concentration of H2O2 application. In this study the effects of H2O2 on growth, development and quality of importance fruit production were discussed. The past research was also discussed about the effects of H2O2 on germination of seedling until maturation, flowering and fruiting stage and fruit quality during pre-harvest and postharvest storage behavior.